Indicators of surgical treatment of patent ductus arteriosus in preterm neonates in the first week of life - Braulio,Renato (2013)
OBJECTIVE: To identify clinical and echocardiographic indicators of the necessity for early surgical closure of patent ductus arteriosus in preterm neonates. METHODS: The prospective study was conducted at the Neonatal Unit of Hospital Municipal Odilon Behrens between 2006 and 2010. The study population comprised 115 preterm neonates diagnosed with patent ductus arteriosus in the first week after birth, of whom 55 (group S) were submitted to clinical and or surgical closure and 60 (group NS) received non-surgical treatment. The parameters analyzed were birth weight, diameter of the ductus arteriosus (DAD), left atrial-to-aortic root diameter ratio (LA:Ao), the quotient of DAD² and birth weight (mm²/kg), and ductal shunting. RESULTS: The study population comprised 58 males and 57 females. The average birth weight of group S (924 ± 224.3 g) was significantly (P=0.049) lower than that of group NS (1012.3 ± 242.8 g). The probability of the preterm neonates being submitted to surgical closure was 62.1% (P=0.006) when the DAD2/birth weight index was > 5 mm²/kg, 72.2% (P=0.001) when the LA:Ao ratio was > 1.5, and 61.2% when ductal shunting was high (P=0.025). CONCLUSION: The parameters DAD²/birth weight index > 5 mm²/kg, LA:Ao ratio > 1.5 and high ductal shunting were statistically significant indicators (P<0.05) of the need for surgical closure of patent ductus arteriosus in low birth weight preterm neonates. Moreover, when an LA:Ao ratio > 1.5 was associated with the occurrence of shock, the probability of surgical closure increased to 78.4%.